AN ANALYTICAL METHOD FOR CHEMICAL SPECIATION OF SELENIUM IN SOIL - Constantin Luca; Mihaela M. Aldea (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Selenium is an essential microelement, sometimes redoubtable, through its beneficial role - risk depending on its concentration in the food chain, at low dose is an important nutrient in the life of humans and animals, contrary at high doses, it becomes toxic. Selenium may be find itself in the environment (soil, sediment, water) in many forms (oxidized, reduced, organometallic) which determine their mobility and toxicity. Determination of chemical speciation (identification of different chemical forms) provides much more complete information for a better understanding of the behavior and the potential impact on the environment. In this work we present the results of methodological research on the extraction of sequential forms of selenium in the soil and the coupling of analytical methods capable of identifying very small amounts of selenium in soils An efficient scheme of sequential extractions forms of selenium (SES) consisting in atomic absorption spectrometry coupled with hydride generation (HGAAS) has been developed into five experimental steps, detailed in the paper. This operational scheme has been applied to the analysis of chemical speciation in the following areas: the Bărăgan Plain and Central Dobrogea of Romania.